2014
DOI: 10.1515/ssa-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the microbiological activity in agricultural and urban soils

Abstract: The aim of this study was to evaluate the enzymatic soil and the number of selected microorganisms in urban soil, which are located in the lane of the reconstructed road and compare it with a soil cultivated for agricultural purposes. The conducted analysis showed significant differences between the results of the soil taken from the roadway and the soil cultivated from agricultural purposes. The C:N ratio in soils of the roadway (from 24 to 31) indicated that they were degraded and heavily degraded soils. Urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Guo et al ( 2010 ), Swędrzyńska et al ( 2013 ), and Wolińska et al ( 2014 ) proved that systematic agricultural practices contribute to a significant decrease in pH values towards acidification, which is one of the causes of soil degradation. Also Dec ( 2014 ) reported that agricultural soils are characterized by a slightly acidic reaction (pH 6.3–6.5). Additionally, our observations might be supported by the findings of Valpassos et al ( 2001 ), who reported that a no-tillage (controls) system showed the highest carbon content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al ( 2010 ), Swędrzyńska et al ( 2013 ), and Wolińska et al ( 2014 ) proved that systematic agricultural practices contribute to a significant decrease in pH values towards acidification, which is one of the causes of soil degradation. Also Dec ( 2014 ) reported that agricultural soils are characterized by a slightly acidic reaction (pH 6.3–6.5). Additionally, our observations might be supported by the findings of Valpassos et al ( 2001 ), who reported that a no-tillage (controls) system showed the highest carbon content.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations performed by Marinkovic et al ( 2012 ) indicated that the highest abundance of ammonifiers was obtained in the case of chernozem, as well as in cambisol and solonetz, while the lowest number was found in fluvisol (8.13 × 10 6 cfu g −1 ). The microbial population and its activity are known to depend greatly on soil pH (Guo et al 2010 ; Swędrzyńska et al 2013 ; Dec 2014 ; Wolińska et al 2014 ), i.e. low pH values significantly decrease microbial activity, and AB abundance was lower in agricultural soils (Wielgosz et al 2010 ; Liu et al 2013 ; Bhuyan et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Soil is one of the most important components of the environment. With respect to its functions in biomass production, carbon sequestration, organic matter decomposition, sorption and storage of mineral as well as organic compounds, it has a multifaceted effect on the natural and cultural environment [1]. Human activity associated with crop production leads to changes in soil properties, and these changes could deteriorate soil quality by hindering the productivity and functioning of natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of the soil is evaluated mainly on the basis of the activity of four enzymes: dehydrogenase, phosphatase, urease, and protease (Dec 2014 ). Often, only dehydrogenase activity is used for this purpose (Kaczyński et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%